A time for creativity: How future-oriented schemas facilitate creativity - KOH, Brandon Yuan Rui (Institutional Knowledge at Singapore Management University, 2017)
According to the creative cognition approach, the infrequent generation of truly creative ideas could be due to the pervasive reliance on schemas during creative ideation. People tasked to generate creative ideas tend to anchor on accessible schemas, thus many of these ideas predictably conform to pre-existing exemplars or concepts. It is reasonable to argue that suppressing the reliance on conventional schemas coupled with activating unconventional schemas could broaden the sources of inspiration and facilitate creativity. Grounded in social schema research, I hypothesize that people tend to project high societal change in the future, and that future construal will activate these change and progress schemas to instigate higher creativity. Results of three experimental studies confirm my mediation prediction that future (vs. present) temporal construal activates schemas of change and progress, which subsequently fosters creative performance in domains that require divergent thinking (albeit not convergent thinking). By experimentally manipulating accessibility of the change and progress schemas under future construal, Study 3 further supports the causal direction in the mediation. I discuss the broad implications of how the study of schematic perceptions about the future contributes to research on creative cognition.